IMPLEMENTASI RESOSIALISASI OLEH DENSUS 88 ANTI TEROR - Nova, Andi; Syauqillah, Muhamad (UI Scholars Hub, 2021)
The Indonesian government takes two distinct approaches to terrorism cases: a soft approach and a hard approach. One of the approaches that has been successful is deradicalization, which is expected to be the most effective method of combating terrorism. The Detachment 88 Task Force is a special unit of the Indonesian National Police tasked with investigating terrorism-related crimes. Officers from Special Detachment 88 deal directly with perpetrators, witnesses, and families affected by terrorism crimes. The purpose of this study is to evaluate the effectiveness of resocialization as the final stage of deradicalization. Resocialization is the stage which the terrorism inmates reintegrate into society and resume full citizenship. This study employs qualitative research, with primary data coming from ex-convicts of post-conviction terrorism and secondary data coming from Densus 88 officers who accompany the resocialization process. This study applies George C. Edward III's implementation theory to assess the communication, resources, both financial and human, disposition, and bureaucratic structure of the task force of Densus 88, Polri Headquarters.